Upward Targeting and Social Protests in China. - Jay Chen, Chih-Jou; Cai, Yongshun (Journal of Contemporary China, 2021)
Protesters in China may face two types of targets. One is the target of blame that is deemed responsible for causing their grievances, whereas the other is believed to be obligated to solve their grievances. Upward targeting occurs when citizens whose grievances are connected to lower-level authorities approach higher-level authorities for solutions. Based on a collection of over 12,000 instances of collective protest in China from 2000 to 2018, this study finds that some groups—such as small groups, veterans, and petitioners—are more likely to resort to upward targeting than others. However, collective actions directed at central authorities are more likely to be suppressed. Blame attribution and the difficulties in coordinating large-scale upward-targeting actions have combined to manifest protest patterns in China.